2017
DOI: 10.1039/c7ra03348f
|View full text |Cite
|
Sign up to set email alerts
|

External oxidant-free cross-coupling of arylcopper and alkynylcopper reagents leading to arylalkyne

Abstract: External oxidant-free cross-coupling of arylcopper and alkynylcopper reagents for the formation of arylalkynes was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The azide formation was confirmed by FT‐IR which showed a characteristic stretching frequency of the azide moiety at 2127 cm −1 and mass spectrometry showed a molecular ion peak [M+K] + at 504.1835. The bulky azide 1 on treatment with copper(I) phenylacetylide [44] in the presence of triazole‐ a NHC ( a NHC=abnormal N‐heterocyclic carbene) [45] in 1,2‐dichloroethane yielded copper(I)‐1,2,3‐triazolide intermediate, which on further treatment with elemental iodine afforded compound 2 in good yield (Scheme 1). The 1 H NMR spectrum of 2 showed a singlet at 2.33 ppm due to methyl protons and aromatic protons appeared as multiplets in the range of 6.93–7.99 ppm, while the CH protons of Ph 2 CH groups resonated at 5.07 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The azide formation was confirmed by FT‐IR which showed a characteristic stretching frequency of the azide moiety at 2127 cm −1 and mass spectrometry showed a molecular ion peak [M+K] + at 504.1835. The bulky azide 1 on treatment with copper(I) phenylacetylide [44] in the presence of triazole‐ a NHC ( a NHC=abnormal N‐heterocyclic carbene) [45] in 1,2‐dichloroethane yielded copper(I)‐1,2,3‐triazolide intermediate, which on further treatment with elemental iodine afforded compound 2 in good yield (Scheme 1). The 1 H NMR spectrum of 2 showed a singlet at 2.33 ppm due to methyl protons and aromatic protons appeared as multiplets in the range of 6.93–7.99 ppm, while the CH protons of Ph 2 CH groups resonated at 5.07 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…CuH decomposes to release H 2 along with the generating of active Cu 0 species [18] . To further verify the carboxylation step of aryl copper(I) in this system, phenyl copper(I) was prepared [19] and reacted with 1 atm CO 2 in the presence of L12 at room temperature (Scheme 3d). The desired product benzoic acid was obtained in 83 % yield, indicating that arylcopper(I) may serve as the key intermediate to perform CO 2 insertion [20] …”
Section: Methodsmentioning
confidence: 99%
“…When reducing the loading of L16 to 10 %, the reaction proceeded smoothly, but the yield of 2 a was reduced to 67 % (Table 2, entry 18). In addition, control experiments revealed that both the copper catalyst and ZnEt 2 were essential to this transformation (Table 2, entries [19][20]. So we selected the conditions mentioned in entry 16 as the standard reaction conditions.…”
mentioning
confidence: 99%
“…24 The compound was obtained as a white solid: 50:1 PE/EA as the eluent; 109.9 mg, 99% yield; 1 1-Methoxy-3-(p-tolylethynyl)benzene (9d). 32 The compound was obtained as a yellow solid: 50:1 PE/EA as the eluent; 104.3 mg, 94% yield; 1 H NMR (400 MHz, CDCl 3 ) δ 7.42 (d, J = 7.8 Hz, 2H), 7.21 (t, J = 7.9 Hz, 1H), 7.12 (d, J = 7.7 Hz, 3H), 7.05 (s, 1H), 6.86 (d, J = 8.3 Hz, 1H), 3.77 (s, 3H), 2.33 (s, 3H); 13 1-Methoxy-2-(p-tolylethynyl)benzene (9e). 33 The compound was obtained as a yellow oil: 50:1 PE/EA as the eluent; 103.2 mg, 93% yield; 1 H NMR (400 MHz, CDCl 3 ) δ 7.46 (dd, J = 13.7, 7.7 Hz, 3H), 7.26 (t, J = 7.9 Hz, 1H), 7.12 (d, J = 7.8 Hz, 2H), 6.95−6.83 (m, 2H), 3.87 (s, 3H), 2.33 (s, 3H); 13 3-(p-Tolylethynyl)pyridine (9f).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%